Impact of a participatory intervention with women's groups on psychological distress among mothers in rural Bangladesh: secondary analysis of a cluster-randomised controlled trial. - Kelly Clarke; Kishwar Azad; Abdul Kuddus; Sanjit Shaha; Tasmin Nahar; Bedowra Haq Aumon; Mohammed Munir Hossen; James Beard; Anthony Costello; Tanja A J Houweling; Audrey Prost; Edward Fottrell (PLoS ONE)
Background Perinatal common mental disorders (PCMDs) are a major cause of disability among women and disproportionately affect lower income countries. Interventions to address PCMDs are urgently needed in these settings, and group-based and peer-led approaches are potential strategies to increase access to mental health interventions. Participatory women's health groups led by local women previously reduced postpartum psychological distress in eastern India. We assessed the effect of a similar intervention on postpartum psychological distress in rural Bangladesh. Method We conducted a secondary analysis of data from a cluster-randomised controlled trial with 18 clusters and an estimated population of 532,996. Nine clusters received an intervention comprising monthly meetings during which women's groups worked through a participatory learning and action cycle to develop strategies for improving women's and children's health. There was one group for every 309 individuals in the population, 810 groups in total. Mothers in nine control clusters had access to usual perinatal care. Postpartum psychological distress was measured with the 20-item Self Reporting Questionnaire (SRQ-20) between six and 52 weeks after delivery, during the months of January to April, in 2010 and 2011. Results We analysed outcomes for 6275 mothers. Although the cluster mean SRQ-20 score was lower in the intervention arm (mean 5.2, standard deviation 1.8) compared to control (5.3, 1.2), the difference was not significant (β 1.44, 95% CI 0.28, 3.08). Conclusions Despite promising results in India, participatory women's groups focused on women's and children's health had no significant effect on postpartum psychological distress in rural Bangladesh.